Edukasi Pra-Nikah Bagi Remaja Di Dusun Pangul Mlati Desa Kepanjen Kecamatan Gumukmas Kabupaten Jember - Beni Ashari, Mella Aulya (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
Realizing a strong and resilient family requires serious efforts, especially for female and male couples who will and are building household magic. Knowledge about creating a happy family, shared awareness in building a healthy and quality family, seriousness in overcoming various family conflicts, and commitment in facing various challenges of increasingly tough global life. The phenomenon of early marriage that occurred in Panggul Mlati Hamlet, Kepanjen Village, Gumukmas District, Jember Regency, still occurs there. The factors that dominate the occurrence of early marriage are cultural/customary factors, religion and economic factors. These three things are considered quite significant from year to year. Cultural/customary factors play a very important role in the occurrence of early marriage, the article is that the Patriarchal culture is still attached. Marriage is a learning process, a process to provide change and knowledge about the world of marriage later. Based on information about the importance of pre-marital education for teenagers: that pre-marital education is very urgent, especially for teenagers, so that later early marriage is slightly reduced there. After conducting pre-marital education for adolescents in the Pelvic Mlati hamlet by providing an understanding of the material about the meaning of gender, sex, and sexuality. The ideal age for marriage, the causes and effects of early marriage itself, as well as the importance of education for them. Indirectly, they immediately realized that they thought that early marriage should have been reduced from now on, especially by emphasizing that education for studying is very important. in order to minimize early marriage by each individual.